Radio & television news. (Ziff-Davis Pub. Co., 1959)
Some issues, Aug. 1948-1954 are called: Radio-electronic engineering edition, and include a separately numbered and paged section: Radio-electronic engineering (issued separately Aug. 1954-May 1955).